Valuasi Ekologi dan Ekonomi Sumber Air Bonleu Kabupaten Timor Tengah Selatan dengan Metode Willingness to Accept - Indriany N.R. Ndoen; Agus A. Nalle; Fredrik L. Benu (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study is a quantitative research that aims to analyze and determine the ecological and economic valuation value of Bonleu water resources in South Central Timor district using the willingnes to accept method. This study is located in a place that uses primary data and secondary data collected using questionnaire methods, observation interviews and focus discussion groups and this study uses data analysis techniques in the form of descriptive statistical analysis methods and continuous valuation method (CVM) methods. The results of this study show that the level of education, land ownership, income, and the number of dependents in the family significantly affect and contribute to the public's perception of the need for environmental service rewards and the amount of environmental service rewards.